Influence of Blood Glucose, Total Protein and Haemoglobin at The Time of Induced Estrus on Conception Rate on Anestrus Crossbred Cows - Salam, Dhasthageer Abdul; Murugave, Kailasam; Raju, Mantena Satyanarayana (The Indian Journal of Animal Reproduction, 2023)
The present study was conducted to evaluate the influence of blood glucose, total protein and haemoglobin at the time of induced estrus on conception rate in 30 postpartum anestrus crossbred dairy cows. The cows were treated with progesterone intravaginal (CIDR) based estrus induction protocol with double fixed timed inseminations at 12 and 24 h after injection of last GnRH. estrus induction response was 100% with majority of the cows (80%) showed intermediate intensity of estrus. On the day of first AI, blood was collected from all the animals for the estimation of glucose, total protein and haemoglobin. The mean time to onset of estrus from the time of removal of CIDR was 44.85 ± 7.23 h. The overall conception rate in the present study was 30 % (9/30). In the present study, the mean values of glucose, total protein and haemoglobin at the time of estrus were 43.81 ± 1.14 mg/dl, 7.78 ± 0.24 g/dl and 8.68 ± 0.22 g/dl respectively. The mean glucose, total protein and haemoglobin levels in the anestrus cows which were included in the study are lower than the normal range. There is no significant different in the biochemical parameters among the cows showing weak, intermediate and intense intensity of estrus. Similarly, there is no significant difference in the biochemical parameters between the cows that conceived and cows not has not conceived. The findings in the present study clearly indicates that poor nutritional status may be the cause for the anestrus condition of the animal under field conditions.